Technology-enabled assessments to enhance multiple sclerosis clinical care and research. Issue 3 (June 2020) - Macaron, Gabrielle; Moss, Brandon P.; Li, Hong; Baldassari, Laura E.; Rao, Stephen M.; Schindler, David; Alberts, Jay L.; Weber, Malory; Ayers, Malissa; Bethoux, François; Boissy, Adrienne; Chizmadia, Desiree; et al.
Abstract : Background: Comprehensive and efficient assessments are necessary for clinical care and research in chronic diseases. Our objective was to assess the implementation of a technology-enabled tool in MS practice. Method: We analyzed prospectively collected longitudinal data from routine multiple sclerosis (MS) visits between September 2015 and May 2018. The MS Performance Test, comprising patient-reported outcome measures (PROMs) and neuroperformance tests (NPTs) self-administered using a tablet, was integrated into routine care. Descriptive statistics, Spearman correlations, and linear mixed-effect models were used to examine the implementation process and relationship between patient characteristics and completion of assessments. Results: A total of 8022 follow-up visits from 4199 patients (median age 49.9 [40.2–58.8] years, 32.1% progressive course, and median disease duration 13.6 [5.9–22.3] years) were analyzed. By the end of integration, the tablet version of the Timed 25-Foot Walk was obtained in 89.0% of patients and the 9-Hole Peg Test in 94.8% compared with 74.2% and 64.3%, respectively before implementation. The greatest increase in data capture occurred in processing speed and low-contrast acuity assessments (0% prior vs 78.4% and 36.7%, respectively, following implementation). Four PROMs were administered in 41%–98% of patients compared with a single depression questionnaire with a previous capture rate of 70.6%. Completion rates and time required to complete each NPT improved with subsequent visits. Younger age and lower disability scores were associated with shorter completion time and higher completion rates. Conclusions: Integration of technology-enabled data capture in routine clinical practice allows acquisition of comprehensive standardized data for use in patient care and clinical research.